2009
DOI: 10.3989/scimar.2010.74n1037
|View full text |Cite
|
Sign up to set email alerts
|

Body morphometrics, swimming diversity and niche in demersal sharks: a comparative case study from the Mediterranean Sea

Abstract: SUmmarY: Seven demersal shark species belonging to six families, obtained from the southern mediterranean Sea, were selected as representative of different putative swimming modes, inhabited depths and trophic levels. caudal fin morphometrics (caudal fin span, area and aspect ratio), hepatosomatic index and muscular-skeletal amount per unit length were estimated and compared within and among species by means of both parametric and non-parametric multivariate and univariate statistical procedures. intra-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
2
9
0
2
Order By: Relevance
“…Despite not explicitly testing for phylogenetic autocorrelation, this study demonstrated that several phylogenetically distant orders -such as Hexanchiformes and Carcharhiniformes (Vélez-Zuazo & Agnarsson 2011) -present similar body shapes, while other more closely related orderssuch as Orectolobiformes and Squaliformes -have different body shapes. Therefore, the body shape of shark orders would not be a reflection of the evolutionary relationship between them, but rather an association with predation strategies and occupation of similar habitats, congruent with the idea that ecomorphological attributes tend to be related to locomotion (Cianciaruso et al 2009) and habitat occupation, as it has already been demonstrated for several shark species (Scacco et al 2010, Irschick & Hammerschlag 2015. These patterns described for sharks were contrasting with those reported to other marine mammals (cetaceans and pinnipeds), which exhibit results supporting the heat conservation hypothesis, but not habitat preference and availability hypotheses (Torres-Romero et al 2016).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Despite not explicitly testing for phylogenetic autocorrelation, this study demonstrated that several phylogenetically distant orders -such as Hexanchiformes and Carcharhiniformes (Vélez-Zuazo & Agnarsson 2011) -present similar body shapes, while other more closely related orderssuch as Orectolobiformes and Squaliformes -have different body shapes. Therefore, the body shape of shark orders would not be a reflection of the evolutionary relationship between them, but rather an association with predation strategies and occupation of similar habitats, congruent with the idea that ecomorphological attributes tend to be related to locomotion (Cianciaruso et al 2009) and habitat occupation, as it has already been demonstrated for several shark species (Scacco et al 2010, Irschick & Hammerschlag 2015. These patterns described for sharks were contrasting with those reported to other marine mammals (cetaceans and pinnipeds), which exhibit results supporting the heat conservation hypothesis, but not habitat preference and availability hypotheses (Torres-Romero et al 2016).…”
Section: Discussionsupporting
confidence: 71%
“…This flattened body shape is common in species thriving in shallower and coastal regions (Kriwet et al 2010, Vaz & de Carvalho 2013 or in reef environments, where they await their prey in ambush strategies (Smith & Brown 2002, Baremore et al 2009, Raoult et al 2017. This type of morphology gives the species a slower and more manoeuvrable swim, typical of benthic species (Scacco et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine if the porbeagle shark's health was adversely affected by microplastic ingestion, we looked for a correlation between the average plastic particle per g w.w. in spiral valves content/tissue and several general health indices. In this case, the Hepatosomatic Index seemed to be the most relevant health indicator in relation to microplastic ingestion, maybe because it relates more directly to toxic effects (Scacco et al, 2010). Some microplastics will be excreted together with the rest of the spiral valve content.…”
Section: Discussionmentioning
confidence: 96%
“…A pesar de que los mecanismos MPF usan sus aletas pares e impares para generar movimientos transitorios y/o nados periódicos, los BCF además de los nados periódicos también permiten una gran maniobrabilidad, y debido a su forma hidrodinámica el análisis cinemático es menos complejo que los MPF [5,7]. En la Figura 3 se presentan los modos de nado correspondientes a los BCF con sus direcciones de nado, en donde el modo anguiliforme es el que presenta un movimiento completamente ondulatorio [13] del cuerpo y el modo thunniforme un movimiento considerado como completamente oscilatorio [20]. De aquí que el ladeo sea mucho mayor en el modo anguiliforme.…”
Section: Figura 1 Clases De Aletas Empleadas En El Movimiento De Un Pezunclassified